Au-IDA microelectrodes modified with Au-doped graphene oxide for the simultaneous determination of uric acid and ascorbic acid in urine samples. (10th February 2017) - Abellán-Llobregat, A.; Vidal, L.; Rodríguez-Amaro, R.; Berenguer-Murcia, Á.; Canals, A.; Morallón, E.
Graphical abstract: Highlights: An electrochemical sensor based on graphene oxide decorated with gold is proposed. The sensor can be used in the simultaneous quantification of UA and AA in urine. Limits of detection of 1.4 μM for AA and 0.62 μM for UA have been obtained. Working ranges between 4.6 μM and 193 μM for AA and between 2 μM and 1.05 mM for UA. Abstract: An electrochemical sensor based on graphene oxide decorated with gold nanoparticles has been prepared for the simultaneous quantification of uric acid (UA) and ascorbic acid (AA) in urine samples. The gold interdigitated microelectrodes array (Au-IDA) has been modified using graphene oxide doped with gold nanoparticles (AuNPs-GO/Au-IDA), which was characterized by TEM, FE-SEM, XPS and cyclic voltammetry. Excellent results were obtained for the separate quantification of UA and AA by chronoamperometry. The electrochemical sensor exhibits limits of detection (LODs) of 1.4 μM and 0.62 μM for AA and UA, respectively, limits of quantification (LOQs) of 4.6 μM (AA) and 2.0 μM (UA), and the working ranges obtained were between 4.6 μM and 193 μM for AA and between 2 μM and 1.05 mM for UA. The repeatability was studied at 20 μM providing coefficients of variation of 16% for AA and 13% for UA. Moreover, UA does not interfere in the measurement of AA and viceversa (provided that the concentration of UA is equal to or higher than 450 μM in the latter case). For lower concentrations of UA, an easy and fast strategy to quantify both analytes is presented. The good electrocatalytic activity achieved with this material makes it useful for the quantification of AA and UA in biological fluids. Other analytes like glucose, dopamine and epinephrine have been investigated. The results allow us to conclude that they do not interfere in the quantification of AA and UA in PBS (0.25 M, pH 7.0). Human urine samples have been analyzed using the method proposed, contaning AA and UA concentration levels of (0.588 ± 0.002) mM and (1.43 ± 0.02) mM, respectively, which are in the concentration range of these analytes in urine samples for healthy people.